COMPARISON OF LOW-TEMPERATURE DECOMPOSITION IN FE-CR AND DUPLEX STAINLESS-STEELS - Miller, M; Hyde, J; Cerezo, A; Smith, G (1995)
A comparison has been made between the aging behavior at 400 degrees C of the ferrite phase of a commercial CF 3 duplex stainless steel and a model Fe-45%Cr binary alloy. The change in the microhardness was found to be substantially higher in the duplex stainless steel than in the iron-chromium model alloy. Atom probe results have revealed that the composition amplitude of the spinodal decomposition is significantly lower in the binary iron-chromium alloy than in the commercial duplex stainless steel. It is therefore concluded that the behavior of binary FeCr alloys does not provide an accurate basis for predicting the extent of the decomposition in the commercial duplex stainless steels.